Manganese enrichment of polymetallic oceanic nodules via selective leaching process for energy storage applications. Issue 5 (21st December 2020) - Mukherjee, Priyanka; Pattnaik, Sushree; Sanjay, Kali; Mohapatra, Mamata
Abstract: BACKGROUND: The FeMn concentrates formed in oceanic nodules serve as highly promising resources for economically‐ and strategically‐important metals, such as manganese, cobalt, nickel, copper, and rare‐earths, among others. Worldwide process flowsheets are being continually developed for maximum extraction of major/minor metal values from the deep‐sea nodules in cost‐effective and environment‐friendly ways. However, a current state‐of‐the‐art technology with zero waste is yet to be developed. RESULTS: The present work's focus was to concentrate Mn in the residue through a single step surfactant mediated leaching process, and the enriched residue has been studied for high‐end energy storage applications. The X‐Ray diffraction pattern of residue obtained from the leaching study using surfactant Triton X‐ 100 matched with α‐manganese oxide, whereas the sample obtained without TX‐100 showed todorokite phases. Under the optimum conditions, dissolution of Mn was restricted to merely 9%, whereas the other metals like Cu, Co, Ni were leached to nearly 85–95% at a temperature of 80 °C at lab scale. Since most of Mn is retained in the residue, it is evaluated for energy storage applications. The specific capacitance value obtained from charge–discharge curves for the material was 110 F g −1 at 0.221A g −1 current density. CONCLUSION: This study proves non‐ionic surfactant TX‐100 enhances leaching of metals like Fe, Co, Ni, and Cu from the manganese nodule at mild operational conditions. On the contrary, it also enriches the Mn content in the leached residue by retarding its dissolution during leaching. The Mn enriched residue has been studied for energy storage applications, which have not been reported in earlier literature. © 2020 Society of Chemical Industry